Caracterização do efeito do tecido adiposo perivascular (PVAT) em aortas de camundongos submetidos a sepse aguda - Naiara de Assis Rabelo Ribeiro (2020)
Perivascular adipose tissue (PVAT) lines the adventitial layer and surrounds most blood vessels. PVAT releases biologically active molecules that regulate vascular tone. Knowing the importance of this tissue in the control of vascular tone and that the systemic hypotension, generated in a case of sepsis, is the main cause of death, this study aimed to study the vasoactive and inflammatory effects of PVAT on aortic hyporeactivity induced by acute sepsis. For this purpose, male Balb / c mice (8 weeks) were used, which were divided into two groups: sham and septic. In the septic group, sepsis was induced by ligation and transverse perforation of the cecum with a 26G needle. In the sham group, the transverse perforation step of the cecum was not performed. 6 hours after sepsis induction, the role of PVAT in vascular tone was assessed in thoracic aortas of the sham and septic groups. Our results demonstrate that although the sham and septic groups have 100% survival, the septic group presented leukopenia marked by neutropenia, hypothermia, arterial hypotension, and a high clinical score when compared to the sham group. Phenylephrine-induced vasoconstriction was significantly reduced in the septic group compared to the sham group in the absence of PVAT. However, in the presence of PVAT, the impairment of vascular contractility observed in the septic group was reestablished. In other words, PVAT presented a vasoconstrictor profile, in contrast to the hyporeactivity caused by sepsis. Among the mechanisms involved in this process, we suggest a reciprocal regulation between reactive oxygen species, in this case, superoxide anion, probably generated from the NADPH oxidase complex, and that by a self-perpetuating cascade, COX-2 and its vasocontractable derivatives, as thromboxane A2 and prostaglandin F2α also act "feeding" this pathway. Therefore, we suggest that the contractile profile presented by PVAT in acute sepsis (6h) is mainly due to the participation of superoxide anions, in addition to derivatives of COX-2 and that both “feed” the cycle favoring the observed contraction.